Application of ground-based, multi-channel microwave radiometer in the nowcasting of intense convective weather through instability indices of the atmosphere - P.W. Chan; K.K. Hon (Meteorologische Zeitschrift, 2011)
A ground-based microwave radiometer gives the possibility of providing continuously available temperature and humidity profiles of the troposphere, from which instability indices of the atmosphere could be derived. This paper studies the possibility of correlating the radiometer-based instability indices with the occurrence of intense convective activity, namely, the occurrence of lightning. The correlation so established could be useful for the nowcasting of convective weather: the weather forecaster follows the evolution of the radiometer-based instability indices in order to access the chance for lightning to occur. The quality of the radiometer-based instability indices is first established by comparing with the radiosonde-based indices. Though there are biases and spreads in the scatter plots of the two datasets, the radiometer-based indices appear to follow the trend of the radiosonde-based indices in spite of the differences in measurement locations and working principles of the two instruments. The thresholds of instability indices for the occurrence of lightning (using 1 discharge) are then determined, specifically for the radiometer in use and the climatological condition in Hong Kong. It turns out that, among all the indices considered in this paper, KI has the best performance in terms of probability of detection of lightning occurrence, particularly for non-summer months, by using an optimum threshold. Finally, the correlation between the instability index and the amount of lightning strokes (within a certain distance from the radiometer) is established. It turns out that the correlation is the best using the minimum value of humidity index, with correlation coefficient of 0.55. The distance from the radiometer considered is about 30 km (having the best correlation between the number of lightning discharges and the instability index), which may be taken as the area over which the radiometer's measurement is considered to be representative of the atmospheric conditions.